Learning Outcomes and Curriculum Development in Psychology. - Lipp, Ottmar; Provost, Stephen; Terry, Deborah J.; Chalmers, Denise; Bath, Debra; Hannan, Greg; Martin, Frances; Farrell, Gerry; Wilson, Peter H. (Carrick Institute for Learning and Teaching in Higher Education, 2006)
Final report on a review of models and methods of teaching, curriculum development and learning outcomes within undergraduate psychology programs in Australian universities. The project sought to identify the disciplinary basis for evaluation; provide an overview of the teaching of psychology in Australian universities; assess the differing programs' capacity to meet the interests and needs of students, employers, the profession, and the scientific discipline; identify innovative practice in the teaching of psychology; develop a platform for future scholarly discussion on the teaching of psychology; develop print and web-based material for dissemination; and establish an evaluation framework for the project.